2012
DOI: 10.1155/2012/428503
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Hydroxyapatite Deposition on a Nanofiber Surface Stimulates Mesenchymal Stem Cell Proliferation and Their Differentiation into Osteoblasts

Abstract: Pulsed laser deposition was proved as a suitable method for hydroxyapatite (HA) coating of coaxial poly-ɛ-caprolactone/polyvinylalcohol (PCL/PVA) nanofibers. The fibrous morphology of PCL/PVA nanofibers was preserved, if the nanofiber scaffold was coated with thin layers of HA (200 nm and 400 nm). Increasing thickness of HA, however, resulted in a gradual loss of fibrous character. In addition, biomechanical properties were improved after HA deposition on PCL/PVA nanofibers as the value of Young's moduli of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 63 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…For instance, conventional CaP coating techniques tend to be harsh and require lengthy processing conditions. To induce Ca 2+ chelating sites for subsequent CaP formation, techniques such as O 2 plasma treatment [5], laser [6], strong alkali (NaOH or KOH) [7] and acid (HNO 3 ) [8] treatments have been used. These harsh processing techniques can cause defects, such as polymer chain scission or changes to polymer properties that may compromise the mechanical strength of the subsequent scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, conventional CaP coating techniques tend to be harsh and require lengthy processing conditions. To induce Ca 2+ chelating sites for subsequent CaP formation, techniques such as O 2 plasma treatment [5], laser [6], strong alkali (NaOH or KOH) [7] and acid (HNO 3 ) [8] treatments have been used. These harsh processing techniques can cause defects, such as polymer chain scission or changes to polymer properties that may compromise the mechanical strength of the subsequent scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current study suggests that composites of PCL/HA-5% and PCL/HA-10% have a great impact on hMSCs proliferation as compared to Neat-PCL and PCL/HA-1% (Figure 4). Cell proliferation, cell cycle, and extracellular matrix are higher when hMSCs were exposed to HA (37, 38, 39, 40). We demonstrated that cellular proliferation was increased in an HA-concentration dependent manner when hMSCs were grown on PCL/HA composites, which is also in agreement with the other studies (4143).…”
Section: Resultsmentioning
confidence: 99%
“…132,133,134 In one study, Zhao et al reported a method for uniform coating of calcium phosphate onto electrospun keratin–PCL composite scaffolds (keratin–PCL). 135 Incorporation of keratin with the PCL decreased its solubility and facilitated homogeneous coating within a short time frame (~ 10 min) by immersing the scaffolds into Ca 2+ and (PO 4 ) 3− solutions separately.…”
Section: Bottom-up Approachesmentioning
confidence: 99%